2021
DOI: 10.3389/fpsyg.2020.613196
|View full text |Cite
|
Sign up to set email alerts
|

An ERP Study of the Temporal Course of Gender–Color Stroop Effect

Abstract: Pink and blue colors have been found to associate with gender stereotypes in previous Western studies. The purpose of the present study was to explore the neuropsychological processing basis of this effect in contemporary Chinese society. We presented stereotypically masculine or feminine occupation words in either pink or blue colors to Chinese college students in a modified Stroop paradigm, in which participants were asked to classify each occupation word by gender as quickly and accurately as possible. Even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…Indeed, blue seems gender-neutral, equally liked by males and females of all ages [9,[51][52][53][54][55][56]. Blue might turn into a symbol of masculinity, or boyhood, only when paired with pink, which in turn is a symbol of femininity and girliness, because pink is avoided by boys, men, and some adult women (see a more in-depth reasoning in [9,57]). In fact, a recent study using a Stroop paradigm demonstrated that masculine words written in pink ink were perceived as being more incongruent than feminine words written in blue ink [57].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, blue seems gender-neutral, equally liked by males and females of all ages [9,[51][52][53][54][55][56]. Blue might turn into a symbol of masculinity, or boyhood, only when paired with pink, which in turn is a symbol of femininity and girliness, because pink is avoided by boys, men, and some adult women (see a more in-depth reasoning in [9,57]). In fact, a recent study using a Stroop paradigm demonstrated that masculine words written in pink ink were perceived as being more incongruent than feminine words written in blue ink [57].…”
Section: Plos Onementioning
confidence: 99%
“…Blue might turn into a symbol of masculinity, or boyhood, only when paired with pink, which in turn is a symbol of femininity and girliness, because pink is avoided by boys, men, and some adult women (see a more in-depth reasoning in [9,57]). In fact, a recent study using a Stroop paradigm demonstrated that masculine words written in pink ink were perceived as being more incongruent than feminine words written in blue ink [57]. As for red, we expected, but did not find a masculinity bias, due to its associations with power and dominance [15][16][17][18].…”
Section: Plos Onementioning
confidence: 99%
“…Thus, pink and blue color cues were sufficient to trigger the activation of gender-related knowledge, indicating the automaticity of category activation from color cues (Bargh, 1999;Macrae & Bodenhausen, 2000). Li et al (2021) examined color-gender Stroop effect (pink-female/blue-male) in Chinese participant and observed that pink but not blue was a "gendered" color, that masculine words in pink ink were perceived as more incongruent than feminine words in blue ink.…”
Section: Introductionmentioning
confidence: 99%
“…Green was selected because it is one of the colors associated with male 7 , 8 and the opposite color of red in many well-established color models 41 . We did not select blue as a choice due to its prevalence as a more preferred color among both males and females 16 , 42 , as well as empirical evidence indicating its lack of gender bias 43 , 44 . Gray was chosen as an achromatic contrasting color that can be matched for saturation and lightness 45 , 46 .…”
Section: Introductionmentioning
confidence: 99%